2021
DOI: 10.1038/s41598-021-84079-y
|View full text |Cite
|
Sign up to set email alerts
|

HPV genotyping and risk factors for anal high-risk HPV infection in men who have sex with men from Toronto, Canada

Abstract: Men who have sex with men (MSM) are disproportionately affected by anal cancer, predominantly caused by high-risk (HR) human papillomavirus (HPV) infection. Currently, the nonavalent HPV vaccine provides coverage against nine HPV genotypes, including seven HR-HPV genotypes. Here, we characterize anal HR-HPV genotype distribution and associated risk factors in MSM from Toronto, Canada recruited between September 2010 and June 2012. Wilcoxon–Mann–Whitney test was used for continuous variables, Chi-square test wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
1
8
1
Order By: Relevance
“…In this case, the lower prevalence of HPV16 was 2.2% in the MSW group, but it went up to 23% prevalence in the MSM group and to 33.7% in those HIVpositive. A similar trend in the prevalence was observed for HPV18, although those were, in general, lower than for HPV16 (0.2% MSW; 8.1% MSM; 16.3% MSM-HIV-positive) (Table 5) [43,77,129,[144][145][146][147]149,150].…”
Section: Molecular-based Hpv Detection Testssupporting
confidence: 70%
“…In this case, the lower prevalence of HPV16 was 2.2% in the MSW group, but it went up to 23% prevalence in the MSM group and to 33.7% in those HIVpositive. A similar trend in the prevalence was observed for HPV18, although those were, in general, lower than for HPV16 (0.2% MSW; 8.1% MSM; 16.3% MSM-HIV-positive) (Table 5) [43,77,129,[144][145][146][147]149,150].…”
Section: Molecular-based Hpv Detection Testssupporting
confidence: 70%
“…Among MSM without HIV from Toronto, current smoking was not associated with the prevalence of any HPV or HR-HPV compared to those not currently smoking. 16 Among MSM without HIV participating in the EXPLORE study, smoking was not associated with the prevalence of HPV. 17 We previously reported risk factors associated with anal HPV prevalent among MSM in the HIM Study , and in adjusted models found no association between smoking and prevalent anal HPV infection.…”
Section: Discussionmentioning
confidence: 96%
“…13 If samples tested positive for beta-globin or an HPV genotype, they were considered adequate and were included in the analysis. The Linear Array assay tests for 37 HPV types, classified as high-risk (HR-HPV; types 16,18,31,33,35,39,45,51,52,56,58,59, and 68) or low-risk (LR-HPV; types 6,11,26,40,42,53,54,55,61,62,64,66,67,69,70,71,72,73,81,82, 82 subtype IS39, 83, 84, and 89). 14 The HPV genotypes were further classified as the HPV types in the 4vHPV vaccine (6/11/16/18) and the 9vHPV vaccine (6/11/16/18/31/33/45/52/58).…”
Section: Anal Specimen Collection For Hpv Detectionmentioning
confidence: 99%
“…This is mainly due to the difficulties in diagnosis and therapeutic control as a result of the well-known prejudices and taboos among the population, mainly since the infection is “fundamentally” linked to intercourse with anal penetration. 5 30 Frequently, the infection is subclinical or remains latent for a long time and presents somewhat different characteristics from those found in other locations. 13 8…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly due to the difficulties in diagnosis and therapeutic control as a result of the well-known prejudices and taboos among the population, mainly since the infection is "fundamentally" linked to intercourse with anal penetration. 5,30 Frequently, the infection is subclinical or remains latent for a long time and presents somewhat different characteristics from those found in other locations. 8,13 Despite the important advances that are being made regarding the treatment of HPV infection, there is no doubt that the best treatment for this disease continues to be prevention through the reduction of risk factors.…”
Section: Introductionmentioning
confidence: 99%